Mitochondrial Stress Induces Plant Resistance Through Chromatin Changes - López Sánchez, Ana; Hernández Luelmo, Sofía; Izquierdo, Yovanny; López, Bran; Cascón, Tomás; Castresana, Carmen (Frontiers in Plant Science, 2021)
Plants respond more efficiently when confronted with previous similar stress. In the case of pathogens, this memory of a previous infection confers resistance to future ones, which possesses a high potential for agricultural purposes. Some of the defense elements involved in this resistance phenotype, as well as epigenetic mechanisms participating in the maintenance of the memory, are currently known. However, the intracellular cascade from pathogen perception until the establishment of the epigenetic memory is still unexplored. Here, through the induction of mitochondrial stress by exogenous applications of Antimycin A in Arabidopsis thaliana plants, we discovered and characterized a role of mitochondrial stress in plant-induced resistance. Mitochondrial stress-induced resistance (MS-IR) is effective locally, systemically, within generation and transgenerationally. Mechanistically, MS-IR seems to be mediated by priming of defense gene transcription caused by epigenetic changes. On one hand, we observed an increment in the deposition of H3K4me3 (a positive epigenetic mark) at the promoter region of the primed genes, and, on the other hand, the DNA (de)methylation machinery seems to be required for the transmission of MS-IR to the following generations. Finally, we observed that MS-IR is broad spectrum, restricting the colonization by pathogens from different kingdoms and lifestyles. Altogether, this evidence positions mitochondria as a prominent organelle in environment sensing, acting as an integrating platform to process external and internal signals, triggering the appropriate response, and inducing the epigenetic memory of the stress to better react against future stressful conditions.